Становлення та етапи розвитку української мови - Воропаєва, К. А. (ХНУРЕ, 2019)
Modem Ukrainian language has been formed for many centuries and has its stages of development, from the second century BC to our time, language, common in south-eastern Europe, belongs to the Slavic group of the Indo-European language family